Communication Sciences and Disorders Students' Clinical and Social Perceptions of Various Speakers. - Lee-Holloway, Shanna Caprice; Lucker, Jay R. (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: The study aimed to analyze speech-language pathology undergraduate and master's students' social perceptions of African American English (AAE) and General American English (GAE) speakers and identify if there is a need for increased awareness regarding respect and acceptance of AAE in training programs. Method: Data were collected via an online survey. Students listened and rated audio samples of AAE and GAE male and female speakers. Results: Descriptive data showed that clinical perception ratings of AAE speakers were generally similar across both schools and between undergraduate and graduate students. However, social perception ratings varied, with historically Black colleges and universities (HBCUs) students and graduate students rating AAE speakers more positively overall compared to students at the predominantly White institutions (PWIs).